2019
DOI: 10.25300/misq/2019/14439
|View full text |Cite
|
Sign up to set email alerts
|

Expecting the Unexpected: Effects of Data Collection Design Choices on the Quality of Crowdsourced User-Generated Content

Abstract: This appendix describes our applicability check in more detail. The purpose of the applicability check (Rosemann and Vessey 2008) was to determine whether attribute data could be transformed to a form (in this case, species level classification) useful to data consumers (in this case, biologists). We also used the applicability check to explore perceptions that biologists in a university setting held about the potential uses and usefulness of data collected using an instance-based approach (versus a class-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 27 publications
0
37
0
2
Order By: Relevance
“…For example, participants who know the objective of the project may overinflate or exaggerate information (Galloway et al 2006;Miller et al 2012). Some have explored the use of tasks which specifically do not require training (Eveleigh et al 2014;Lukyanenko et al 2019), while others have investigated the possibility of attracting diverse crowds so that training induced biases are mitigated due to the diversity of the participants (Ogunseye et al 2017;Ogunseye and Parsons 2016). All these are novel ideas for traditional information quality research.…”
Section: Training and Evaluating Learning And Performancementioning
confidence: 99%
See 1 more Smart Citation
“…For example, participants who know the objective of the project may overinflate or exaggerate information (Galloway et al 2006;Miller et al 2012). Some have explored the use of tasks which specifically do not require training (Eveleigh et al 2014;Lukyanenko et al 2019), while others have investigated the possibility of attracting diverse crowds so that training induced biases are mitigated due to the diversity of the participants (Ogunseye et al 2017;Ogunseye and Parsons 2016). All these are novel ideas for traditional information quality research.…”
Section: Training and Evaluating Learning And Performancementioning
confidence: 99%
“…Thus, holding data contributors to data consumer standards may curtail their ability to provide high quality content as defined by data consumers, or suggest a need to refine instructions, procedures, or expectations. Guided by this definition, a series of laboratory and fields experiments demonstrated that accuracy and completeness of citizen science data can indeed be improved by relaxing the requirements to comply with data consumer needs (Lukyanenko et al 2014a(Lukyanenko et al , 2014bLukyanenko et al 2019), which is a standard project design strategy for achieving data quality targets in citizen science. Further, for projects focusing on new, emerging phenomena, it may be challenging to anticipate the optimal structure of citizen science data due to the different needs of diverse data consumers, so traditional solutions for storage premised on a priori structures (e.g., relational databases) may be inadequate in this setting (Sheppard et al 2014).…”
Section: Re-examining Is Research Assumptionsmentioning
confidence: 99%
“…Lukyanenko et al ( 2019a , p. 7) state that despite the importance for the society and the relatedness to our discipline IS “[…] continues to lag behind such disciplines as biology and education in working with citizen science as a context for research.” Disciplines like biology, conservation, and physics are much more active here (demonstrated clearly by Lukyanenko et al 2019b ). Although there are some academic articles in IS literature on citizen science there is still a lack of citizen science projects with clear IS research questions.…”
Section: Citizen Sciencementioning
confidence: 99%
“…Such a technique might be used as an automatic reconciliation system that treats every new contribution of sets of attributes as raw data and, simultaneously, as training data for an instance. A recent study, for example, demonstrates the potential of machine learning classification by classifying finegrained crowdsourced data into more useful coarsegrained data with reasonable accuracy [47]. Further explorations of how to use similar artificial intelligence tools to enhance the utility of crowdsourced data is a potent area for future research.…”
Section: Future Directionsmentioning
confidence: 99%